2022
DOI: 10.23736/s0022-4707.21.12911-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of phase angle and appendicular upper and lower body lean soft tissue with physical performance in young elite soccer players: a pilot study

Abstract: The final version may contain major or minor changes.Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Even though the present sample size was in line with previous studies in team sport athletes [ 48 , 49 ], its small size limits the interpretation of the results as well as their generalization. Further studies with a larger sample are warranted.…”
Section: Discussionsupporting
confidence: 51%
“…Even though the present sample size was in line with previous studies in team sport athletes [ 48 , 49 ], its small size limits the interpretation of the results as well as their generalization. Further studies with a larger sample are warranted.…”
Section: Discussionsupporting
confidence: 51%
“…For example, Martins et al [ 13 ] reported that young soccer players with higher whole-body PhA values had better performance in sprinting speed and repeated-sprint ability. Likewise, a recent study reported a significant correlation between whole-body PhA (WBPhA) and vertical-jump (positive correlation) and sprint performance (inverse correlation) in youth soccer [ 14 ]. Moreover, Nabuco et al [ 15 ] showed that WBPhA was inversely associated with perceived fatigue and positively related with sprint performance in soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…This may be of interest, since changes in fat-free mass, which includes muscle mass and body fluids, could negatively affect tolerance to high training exposure, possibly increasing the risk of injury [ 7 ]. In addition, muscle mass seems related to anaerobic performance in soccer players, given that its decrements correlated to decrements in sprinting and jumping capacity [ 8 ]. Therefore, monitoring these components of fat-free mass may also be relevant.…”
Section: Introductionmentioning
confidence: 99%